The D405N Mutation in the Spike Protein of SARS-CoV-2 Omicron BA.5 Inhibits Spike/Integrins Interaction and Viral Infection of Human Lung Microvascular Endothelial Cells - Antonella Bugatti; Federica Filippini; Serena Messali; Marta Giovanetti; Cosetta Ravelli; Alberto Zani; Massimo Ciccozzi; Arnaldo Caruso; Francesca Caccuri (Viruses, 2023)
Severe COVID-19 is characterized by angiogenic features, such as intussusceptive angiogenesis, endothelialitis, and activation of procoagulant pathways. This pathological state can be ascribed to a direct SARS-CoV-2 infection of human lung ECs. Recently, we showed the capability of SARS-CoV-2 to infect ACE2-negative primary human lung microvascular endothelial cells (HL-mECs). This occurred through the interaction of an Arg-Gly-Asp (RGD) motif, endowed on the Spike protein at position 403–405, with αvβ3 integrin expressed on HL-mECs. HL-mEC infection promoted the remodeling of cells toward a pro-inflammatory and pro-angiogenic phenotype. The RGD motif is distinctive of SARS-CoV-2 Spike proteins up to the Omicron BA.1 subvariant. Suddenly, a dominant D405N mutation was expressed on the Spike of the most recently emerged Omicron BA.2, BA.4, and BA.5 subvariants. Here we demonstrate that the D405N mutation inhibits Omicron BA.5 infection of HL-mECs and their dysfunction because of the lack of Spike/integrins interaction. The key role of ECs in SARS-CoV-2 pathogenesis has been definitively proven. Evidence of mutations retrieving the capability of SARS-CoV-2 to infect HL-mECs highlights a new scenario for patients infected with the newly emerged SARS-CoV-2 Omicron subvariants, suggesting that they may display less severe disease manifestations than those observed with previous variants.